Projeto aerodinâmico de pás de uma turbina eólica - Morais, George Lopes (Universidade Federal Rural do Semi-Árido, 2018)
The present work aims to design blades of a wind turbine of small horizontal axis, starting from a simplified methodology to determine an aerodynamic profile, followed by obtaining the rope of each element and its respective forces acting on each element. This study is fundamental for the design of a wind turbine, since the blades interact with the wind, being the component responsible for capturing part of the energy of the wind. Through the XFLR5 computational tool, aerodynamic simulations were performed with the purpose of obtaining parameters of each profile analyzed and with that to define the best profile for application in a small wind turbine. The selected profile performed well given the design conditions.
Monografia
Keywords: Energia renovável; Aerogerador; Projeto aerodinâmico; ENGENHARIAS::ENGENHARIA MECANICA